Electrochemiluminescent analyzer elan-3d for assay and research - Zholudov, Yu. T.; Rozhitskiy, M. M. (ХНУРЭ, 2009)
The work is devoted to development of automated electrochemiluminescent analyzer ELAN-3d aimed at electrochemical/ electrochemiluminescent (ECL) assays including biomedical and environmental applications. The developed device fills the gap of inexpensive ECL equipment aimed at research work. ELAN-3d consists of external unit containing potentiostat and PMT module in a light proof box and PC for control. The external unit is connected to PC via Advantech PCI-1711 data acquisition card. ELAN-3d is mainly intended for investigation of new ECL compositions, development of sensors and assay methods, study of new electrode materials.